(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Traumatic ossicular chain disruption is an important cause of persistent conductive hearing loss following head trauma. Early diagnosis and appropriate surgical intervention are essential for restoring hearing. Ossiculoplasty is commonly performed to reconstruct the ossicular chain and improve auditory outcomes. However, hearing rehabilitation outcomes may vary depending on the type of ossicular injury and reconstruction technique used. Objective: To evaluate the management strategies and hearing rehabilitation outcomes in patients with traumatic ossicular chain disruption. Materials and Methods: This prospective observational study was conducted in the Department of Otorhinolaryngology at IMS & SUM Hospital, Bhubaneswar, from September 2023 to December 2025. A total of 30 patients aged 18–60 years with conductive hearing loss due to traumatic ossicular disruption were included. All patients underwent detailed clinical examination, otoscopic evaluation, pure tone audiometry, and high-resolution computed tomography (HRCT) of the temporal bone. Patients with confirmed ossicular chain disruption underwent exploratory tympanotomy followed by ossiculoplasty. Hearing outcomes were assessed by comparing preoperative and postoperative air-bone gap (ABG) values over a 12-month follow-up period. Results: The majority of patients were male (66.7%). Road traffic accidents were the most common cause of trauma (46.7%). Incudostapedial joint dislocation was the most frequent ossicular injury observed. The mean preoperative air-bone gap was 34.6 ± 6.8 dB, which improved significantly to 13.2 ± 4.5 dB at 12-month follow-up. Successful hearing improvement (ABG ≤ 20 dB) was achieved in 83.3% of patients. Titanium partial ossicular replacement prosthesis and autologous incus interposition were the most common reconstruction techniques used. Conclusion: Traumatic ossicular chain disruption is a significant cause of conductive hearing loss following head injury. Early diagnosis and appropriate surgical reconstruction provide favorable hearing rehabilitation outcomes.